A diagnostic immunohistochemical panel for yolk sac (primitive endodermal) tumours based on an immunohistochemical comparison with the human yolk sac. Issue 1 (13th March 2014) - Nogales, Francisco F; Quiñonez, Enoe; López‐Marín, Laura; Dulcey, Isabel; Preda, Ovidiu
<x xml:space="preserve">Abstract</x> Aims To establish a diagnostic immunohistochemical panel for various histotypes of yolk sac (primitive endodermal) tumours (YSTs) by comparison with the human yolk sac (HYS) immunophenotype. Methods and results Twenty‐five YSTs showing either classical patterns (CPs) of histology (microcystic/reticular, n = 14; polyvesicular, n = 1; and hepatoid, n = 1) or somatic glandular patterns (SGPs; n = 9) were analysed for expression of α‐fetoprotein (AFP), glypican‐3 (GPC3), villin, hepatocyte paraffin‐1 (HepPar‐1), CDX2, SALL4 and LIN28. AFP expression was constantly heterogeneous in CPs but tended to be focal/absent in SGPs. GPC3 was diffuse in CPs but heterogeneous (seven cases) or focal/absent (two cases) in SGPs. HepPar‐1 expression was focal in all but three cases (diffuse in one CP‐hepatoid and two SGPs). CDX2 positivity was focal in CPs but heterogeneous (seven cases) or diffuse (two cases) in SGPs. Villin, SALL4 and LIN28 were diffusely positive in nearly all cases. Conclusions CPs reproduce the immunophenotype of HYS and early endoderm with variable expression of both AFP and markers of early gut or hepatic differentiation. SGPs with intestinal differentiation often have incomplete immunophenotypes. A differential diagnosis panel, including both markers of pluripotentiality (SALL4 and/or LIN28) and endoderm (AFP, GPC3 and villin), is proposed. It identifies overlapping multidifferentiation of primitive and somatic immunophenotypes, supporting the recently proposed term of primitive endodermal tumours.